Accuracy of intraocular lens power formulas for eyes with scleral-sutured intraocular lenses in congenital ectopia lentis. Issue 4 (April 2022) - Lian, Zhangkai; Cao, Qianzhong; Qi, Haotian; Young, Charlotte Aimee; Zhang, Xinyu; Jin, Guangming; Zheng, Danying
Abstract : For CEL patients with scleral-sutured IOL surgery, the SRK/T and EVO formulas were 2 of the recommended IOL formulas that had the lowest PEs after constant optimization. Abstract : Purpose: To compare the accuracy of intraocular lens (IOL) power calculation formulas in eyes with congenital ectopia lentis (CEL) that underwent scleral-fixated IOL implantation. Setting: Zhongshan Ophthalmic Center, Guangzhou, China. Design: Retrospective consecutive case-series study. Methods: 158 eyes from 158 patients diagnosed from December 12, 2017, to November 16, 2020, with CEL and undergoing a lensectomy and scleral fixation of a Rayner 920H or 970C model IOL were retrospectively reviewed. The prediction errors (PEs) of the spherical equivalent of 8 formulas, Barrett Universal II (BUII), Emmetropia Verifying Optical (EVO), Haigis, Hoffer Q, Holladay 1, Kane, Hill-RBF 3.0, and SRK/T, were compared. Results: For CEL patients with scleral-sutured IOL, all 8 formulas yielded myopic PEs without constant optimization. After such optimization, the performance of each formula ranked by median absolute error (MedAE) from the lowest to highest in diopter (D) was as follows: SRK/T (0.47), EVO (0.48), Kane (0.52), BUII (0.53), Hoffer Q (0.58), Holladay 1 (0.59), Haigis (0.61), and Hill-RBF 3.0 (0.62) formulas. The EVO and SRK/T formulas had the highest prediction accuracy concerning the percentage of cases within ±0.50 D and ±1.00 D range of PE in eyes that experienced scleral-sutured IOL surgery, respectively. Conclusions: All formulas before constant optimization produced myopic PEs. After optimization, the SRK/T and EVO formulas had the lowest MedAE and the highest percentage of PE in the range within ±0.50 D for CEL patients with scleral-sutured IOL implantations.